Cardiac arrest in the paediatric intensive care unit: defining the problem and developing solutions. Issue 4 (17th December 2020) - Ray, Candice M; Pizzuto, Matthew; Reyes-Alvarado, Edith; Jackson, Kimberly; Turner, David A; Kamath, Sameer
Abstract : Thousands of children experience a cardiac arrest event in the hospital each year, with more than half of these patients not surviving to hospital discharge. Cardiopulmonary resuscitation (CPR) depth, rate, velocity and percentage of high-quality chest compressions are modifiable factors associated with improved survival. Therefore, we created a novel and standardised process to track and analyse cardiac arrests in the Duke paediatric intensive care unit (PICU). Our aim was to identify areas for improved American Heart Association (AHA) compliance and implement education and communication-based initiatives to enhance early recognition of at-risk patients leading to improved outcomes. From January 2017 to December 2018, all cardiac arrests in our PICU were tracked, reviewed and presented at monthly morbidity and mortality conference. We used the data to track compliance with AHA guidelines and identify opportunities for improvement. Through these efforts, we established a multidisciplinary cardiac arrest education and review programme. Over the 2-year period, we tracked 45 cardiac arrests, which comprised 2% of all PICU admissions. In 2017, during the first year of development, 16 of 22 arrests (73%) were not reported to code committee members in time for complete review. Of the six cardiac arrests with complete reviews, only 17% followed AHA guidelines. In 2018, all 23 arrest events were communicated and 76% of resuscitations were found to be compliant with AHA guidelines. Survival of patients to discharge was 47% in 2017 and increased to 63% in 2018 with similar percentage of PICU admissions having a cardiac arrest between the 2 years. The primary aim of this project was to establish a multidisciplinary comprehensive cardiac arrest review process. This programme allowed for comprehensive analysis of individual events, promoted quality improvement initiatives and improved consistent delivery of high-quality CPR.